Flexural behavior of concrete beam reinforced with bundled bars - Muhammad Amirul Ab. Kader, 1993-, author; Izni Syahrizal Ibrahim, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2016